PERAN BANK SEBAGAI LEMBAGA PERANTARA (INTERMEDIARY) DITINJAU DARI UNDANG-UNDANG NOMOR 10 TAHUN 1998 - SUMARNI, SUMARNI (Universitas Mahasaraswati Mataram, 2021)
The purpose of this study was to determine the role of banks as intermediary institutions in terms of Law Number 10 of 1998. To answer the problem formulation, the author uses normative legal research, namely by studying / analyzing primary and secondary legal materials by understanding law as a set of rules or positive norms in the statutory system that governs the issues under study. Based on the results of the study, it is concluded that the bank as one of the most important financial institutions and has a major role in people's lives has a function, namely First is as a fund trader (money lender), namely a vehicle that can collect and channel public funds effectively and efficiently. The bank becomes a place for safekeeping and safekeeping of money, which in practice serves as a sign of safekeeping and safekeeping of the money, so the custodian and the depositor shall be given a sheet of paper and proof. Meanwhile, in its function as a channel of funds, the bank provides credit or includes it in the form of securities. The second is as an institution that launches trade transactions and payments of money. The bank acts as a liaison between one customer and another if both make transactions. In this case the two persons do not directly make the payment but pay enough attention to the bank to settle it